Smart grids and power system reliability - Dilparic Cakić, Milica; Ristić, Mihajlo (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
The paper deals with smart grids and the reliability of the power system. Smart Grids have emerged as a strategy to increase the efficiency of energy systems around the world. Based on the analysis of Smart Grid implementation, liberalization of the electricity market and system reliability, it is concluded that Smart Grid has not raised the reliability of the power system, but raises it only by constant investment in production and capital plants of the system, with optimal use of smart grids. and smart measurements, without impoverishing the power industry. The paper presents the disintegration of the system in calm weather, low quality of delivery where smart grids did not help enough.
Keywords: smart grids, power system reliability, system breakdowns, low quality electricity supply